Emigrant dreams, immigrant borders : migrants, transnational encounters, and identity in Spain - Vega-Durán, Raquel (Emigrant Dreams, Immigrant Borders, 2016)
This interdisciplinary book offers a fresh way to understand present-day Spain in relation to its African and Latin American migrants. It combines readings of a large range of cultural works with a clear understanding of political, historical, and social context, in order to rethink migrant identities, their complex cultural representations, and the transnational conceptions of Spain that emerge from the encounter with the foreigner. It offers new comprehensive theories on the border and the Other.